If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 5(3x + -10) + -5x Reorder the terms: 15 = 5(-10 + 3x) + -5x 15 = (-10 * 5 + 3x * 5) + -5x 15 = (-50 + 15x) + -5x Combine like terms: 15x + -5x = 10x 15 = -50 + 10x Solving 15 = -50 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 15 + -10x = -50 + 10x + -10x Combine like terms: 10x + -10x = 0 15 + -10x = -50 + 0 15 + -10x = -50 Add '-15' to each side of the equation. 15 + -15 + -10x = -50 + -15 Combine like terms: 15 + -15 = 0 0 + -10x = -50 + -15 -10x = -50 + -15 Combine like terms: -50 + -15 = -65 -10x = -65 Divide each side by '-10'. x = 6.5 Simplifying x = 6.5
| -6.8(4x+6)-1.7(3x-5)= | | 16y=112 | | 3(80x-9x)=x-96 | | 8a-6a+3=7 | | 16=12-x | | 3m-9n=2 | | 2g-5=6 | | 2z-3=4z-1 | | 6a^2+12a-48=0 | | 36=3x+2+6x+7 | | (2x+5)8=72 | | -36-52= | | 4.5-1.5(6m+2)=3 | | 7+3*4-1=39 | | 3y-4(y+2)=2(3y-2) | | -1-10(10r+6)= | | -3n-5n=8 | | 5x^2+5y=45 | | 3z-9=3 | | -2x+6=16 | | 7p=35 | | (x-5)(x-6)=6 | | 4x-7=7x-5 | | x^4-17x^2+52=0 | | 3a-15=-6 | | 3y/2=-6 | | 4x+20=53-2x | | y=7x^2-x+11 | | V^2-2v=4v+40 | | 17=(3x) | | 5x/6=30 | | 0.2x=10 |